The evaluation of trace elements and associated risk in the polar ecosystem of the Fildes Peninsula, Antarctica - Ni, Zhixin; Chen, Xin; Du, Sen; Lu, Chuqian; Luo, Guangfu; Zhou, Peng; Du, Weimeng; Qi, Luyang; Chen, Changshu; Deng, Wei; Dang, Aicui (Frontiers in Marine Science, 2024)
The behavior and influence mechanisms of trace elements in Antarctic ecosystems are particularly complex and important. This study aims to assess the ecological risk to the Fildes Peninsula by systematically analyzing the distribution of trace elements, and provides a scientific basis for the protection of the Antarctic ecosystem. Trace element concentrations in the soils of the Fildes Peninsula are highest for Fe, Al, and Mg, with notable differences in distribution due to varying topographies and landscapes. Principal component analysis reveals strong correlations among Zn, Fe, Mn, Co, and Cu, and distinct patterns for Na, Ca, As, and Cr. Moss demonstrates a high enrichment capacity for Cu and Zn, often accumulating them to higher levels than soil, with significant spatial variation observed. The bioaccumulation factors (BAF) for K and Ag exceed 1 at all 12 stations, indicating a high capacity for bioaccumulation. Over half of the stations show BAF values greater than 1 for Na, Ca, and Cd, while the other trace elements have BAF values greater than 1 at only limited stations. The geo-accumulation index (Igeo) shows most trace elements in the Fildes Peninsula soils are unpolluted, with Mg, Mn, Cr, and Ni concentrations varying between unpolluted and moderate pollution, and all potential ecological risk index (PERI) values under 150 indicating low ecological risk.